Therapeutic challenges in a patient with the simple virilizing (SV) form of congenital adrenal hyperplasia (CAH) due to the P30L/I172N genotype - Maja Tankoska; Violeta Anastasovska; Marina Krstevska-Konstantinova; Michel Naydenov; Mirjana Kocova (Walter de Gruyter GmbH, 2019)
Background Steroid 21-hydroxylase deficiency is an autosomal recessive disorder, present in 90-95% of all cases with congenital adrenal hyperplasia (CAH). The classical simple virilizing (SV) form of the disease causes virilization of the external genitalia in newborn females and pseudo-precocious puberty in both sexes, due to reactive androgen overproduction. Case presentation We describe a 3.5-year-old girl presenting with pubarche, P2 according to Tanner, advanced bone age of 6 years and 10 months, and high serum levels of 17-hydroxyprogesterone (17-OHP). Molecular analysis of the nine most common pseudogene-derived CYP21A2 point mutations was performed in the patient and her family members using the polymerase chain reaction/amplification-created restriction site (PCR/ACRS) method. We detected the P30L/I172N genotype in the patient. She had inherited a mild P30L mutation from her mother and a severe I172N mutation from her father. Conclusions Although the CAH phenotype is determined by the allele that produces most of the enzyme activity and the mild non-classical (NC) phenotype should be expected, the mild P30L known to be more virilizing probably induced the classical SV phenotype in our patient. A continuous regimen of hydrocortisone at a recommended dose failed to decrease the 17-OHP sufficiently. Careful tapering of the dose did not help, and her pubic hair advanced to P3 according to Tanner. Individually tailored treatment is warranted in this patient.